(untitled) (Journal of Hama University, 2024)
The research aims to measure the impact of the ownership structure with its components (concentration of ownership - institutional ownership - foreign ownership - administrative ownership) on the added value of the intellectual capital of banks listed on the Damascus Stock Exchange. The statistical population for the study consists of (11) banks listed on the Damascus Stock Exchange, after excluding Islamic banks, during the period extending from 2017 to 2021. Through the use of regression analysis. The results of the study showed that after controlling for the size of the bank, some components of the ownership structure (concentration of ownership) had a significant and positive effect on the added value of intellectual capital, while there was no effect of institutional, foreign and administrative ownership on the added value of intellectual capital for banks listed on the Damascus Stock Exchange Finance.